A small case series of primary synovial sarcoma of lung - Nitesh, Anand; Nandennavar, Manjunath; Karpurmath, Shashidhar V.; Kupati, Shailaja (International Journal of Research in Medical Sciences, 2024)
Primary synovial sarcoma of lung (PSSL) is extremely rare accounting for <0.5% of all lung tumors. Less than hundred cases of primary synovial sarcoma of the lung (PSS) have been reported. Thus, very limited medical literature is available regarding the clinical presentation and treatment outcomes of PSSL. Here we highlight the clinico-pathological features, immunohistochemistry, and treatment outcomes of a series of three PSSL cases. The mean age was 70 years and male to female ratio was 2: 1. Chest pain was the most common presenting complaint. Tumor size was more than 5 cm in all the cases. The characteristic biopsy finding was round and short spindled cells. IHC was strong positive for TLE 1 with final diagnosis being biphasic synovial sarcoma for all the three cases. Surgery was offered to all cases but only one was deemed fit for surgery. One received ifosfamide/epirubicin based chemotherapy while the third patient expired after one month of pazopanib. In few recent series, PSSL is being reported as the most common subtype of primary lung sarcoma comprising 14.7% to 18% of all primary lung sarcomas, due to wider utilization of immunohistochemical and cytogenetic analysis. The diagnosis requires clinico-pathologic and immunohistochemical investigations to exclude other primary and metastatic lung sarcoma. Thus, it merits to be in one of the differentials of primary lung masses not categorised as lung carcinomas.